Novel Fungal Pathogenicity and Leaf Defense Strategies Are Revealed by Simultaneous Transcriptome Analysis of Colletotrichum fructicola and Strawberry Infected by This Fungus - Zhang, Liqing; Huang, Xin; He, Chengyong; Zhang, Qing-Yu; Zou, Xiaohua; Duan, Ke; Gao, Qinghua (Frontiers in Plant Science, 2018)
Colletotrichum fructicola, which is part of the C. gloeosporioides species complex, can cause anthracnose diseases in strawberries worldwide. However, the molecular interactions between C. fructicola and strawberry are largely unknown. A deep RNA-sequencing approach was applied to gain insights into the pathogenicity mechanisms of C. fructicola and the defense response of strawberry plants at different stages of infection. The transcriptome data showed stage-specific transcription accompanied by a step-by-step strawberry defense response and the evasion of this defense system by fungus. Fungal genes involved in plant cell wall degradation, secondary metabolism and detoxification were up-regulated at different stage of infection. Most importantly, C. fructicola infection was accompanied by a large number of highly expressed effectors. Four new identified effectors function in the suppression of Bax-mediated programmed cell death. Strawberry utilizes pathogen-associated molecular patterns (PAMP)-triggered immunity and effector-triggered immunity to prevent C. fructicola invasion, followed by the initiation of downstream innate immunity.The up-regulation of genes related to salicylic acid provided evidence that salicylic acid signaling may serve as the core defense signaling mechanism, while jasmonic acid and ethylene pathways were largely inhibited by C. fructicola. The necrotrophic stage displayed a significant up-regulation of genes involved in reactive oxygen species activation. Collectively, the transcriptomic data of both C. fructicola and strawberry shows that even though plants build a multilayered defense against infection, C. fructicola employs a series of escape or antagonizing mechanisms to successfully infect host cells.